1987
DOI: 10.3397/1.2827683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Design of Transmission Rooms on the Sound Transmission Loss of Glass--Intensity Versus Conventional Method

Abstract: An elaborate experimental study is c a r r i e d out on the effect of the design of sound transmission r o o m s on the sound transmission loss of a l a m i n a t e d glass panel. Systematic comparisons have b e e n m a d e b e t w e e n the results o b t a i n e d by the sound intensity m e t h o d and the conventional t w o -r o o m m e t h o d . R e s e a r c h has b e e n done to learn the influence of the niche, the r o o m volumes, the loudspeaker and microphone positions, the m e a s u r i n g direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Concerning reproducibility, significant differences can be observed in the sound reduction index when measured in different laboratories, especially at low frequencies [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning reproducibility, significant differences can be observed in the sound reduction index when measured in different laboratories, especially at low frequencies [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…2 (M) ¼ / R (x M ,y M ) and the modal expansion ofp 2 [Eq. (5)] in the resulting equation, one ends up with…”
Section: E Equations Of the Coupled Systemmentioning
confidence: 99%
“…1,2 Several experimental studies revealed that the values of STL depend on the location of the sample in the tunnel. [3][4][5][6][7] For subcoincidence frequencies, a lower STL is achieved when the sample is located in the middle position along the tunnel depth compared to the case without tunnel or compared to the case where the sample is flush mounted at one end of the tunnel. The STL is also affected by the lateral size and the depth of the tunnel.…”
mentioning
confidence: 99%
“…This paper was reprinted in the Noise Control Engineering [33] . There were some researchers to develop relevant study subsequently [34][35][36][37] . R.E.Halliwell et al compared the sound intensity method to the sound pressure method under different measurement conditions.…”
Section: The Development Of the Sound Insulation Measurement Usingmentioning
confidence: 99%